Microorganism composite fungus agent for promoting agricultural waste quickly rotten and its making method - MINGLEI LI; HUA GAO; JIE GU (2004)
A composite bacteria preparation for quickly putrefying agricultural waste is composed of living bacteria (bacillus, actinomycess, yeast and fungus) and adsorptive carrier (zeolite, bran, bone powder, fish powder and brown sugar). Its advantages are high putrefying efficiency, low cost, less loss of nutrients and improving soil. 本发明涉及一种促进农业废弃物快速腐解的微生物复合菌剂及制作方法，其腐解效率高，腐殖质化程度强，使用成本低，腐解过程中养分流失少，并且腐解产物中具有大量的有效微生物，可以改善土壤微环境。本发明包括由细菌、放线菌、酵母菌、真菌组成的微生物活菌体以及吸附载体，吸附载体包括沸石、麸皮、骨粉、鱼粉、红糖，微生物活菌体与吸附载体的比例为：微生物活菌体∶吸附载体＝2∶98，微生物活菌体各组分的比例为：细菌∶放线菌∶酵母菌∶真菌＝3∶3∶3∶1。